Resilience mechanisms of social enterprises in times of crisis - Utama, Radikal Yuda; Bhatt, Babita (Communications in Humanities and Social Sciences, 2024)
Unlike typical organizations, social enterprises are considered inherently vulnerable in view of their integration of two distinct institutional logics: economic and social. This duality, however, also positions social enterprises as a crucial societal agent, particularly in Indonesia, for addressing any intricate social issues. In turn, this research aims to examine the challenges, resilience sources, and strategies that social enterprises employ to maintain resilience during crises. Semi-structured interviews were conducted with five social enterprise founders and utilize the framework analysis technique to analyze data collected. Data triangulation was achieved by supplementing interview data with secondary sources, including reports, websites, and social media from all participants. The study identified two primary resilience sources: internal and external factors. Notably, the resilience process can be articulated through four mechanisms: social imprinting, community dynamics, weak ties, and Gotong Royong (mutual cooperation). This research aims to contribute to the theoretical understanding of social enterprise resilience and relationships, while also offering practical insights for social enterprises to enhance their resilience.